Securing untrusted memories in embedded systems with dynamic integrity checking - Tay, Cedric Jinteng (2016)
This report presents a framework for generating a memory integrity tree to demonstrate the success of securing untrusted memories in embedded systems with dynamic integrity checking. The development is a follow-up work of a previous student in Year 2015 which has developed a C-language program for memory authentication using TEC-Tree on an embedded system implemented on NIOS II Processor. Analysis is first carried out on the previous work/ program to identify the limitations and constraints. The main focus of this project is to create a framework to automate the generation of an efficient TEC-Tree. This efficient tree allows the flexibility to have any number of data while removing redundancy. In addition, the proposed framework can generate trees of varying bit-size as well as enabling any number of children for each parent node of the tree in order to increase the efficiency. The code/ program development work is based on C-language and the embedded system using NIOS II Processor. Experiments are performed and results are analyzed to determine the efficiency of the new code/ program in term of timings for Read and Write functions as compared to previous project.